1998
DOI: 10.1007/bf02672512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical training on bone mineral density in prepubertal girls: A comparative study between impact-loading and non-impact-loading sports

Abstract: Physical activity is known to have an anabolic effect on bone tissue. It has been shown to increase the bone mineral density (BMD) in young adults, as well as in teenagers. But there is little information about the effect of intensive physical activity in childhood, particularly at the prepubertal stage. To examine the influence of an early intensive physical training on BMD, we have studied a group of elite prepubertal girls, at the starting phase of their peak bone mass acquisition. Subjects were engaged eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
123
3
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(141 citation statements)
references
References 38 publications
11
123
3
4
Order By: Relevance
“…The so far published prospective controlled exercise intervention studies, most elegant support this view (14)(15)(16)(18)(19)(20), whereas similar effects could not be found in the post-pubertal period (12). Furthermore, published data indicate that the physical activity ought to include high-impact activities (21)(22)(23)(24) and that the training should probably be initiated before or in early puberty (25), if the purpose is to reach the most beneficial anabolic skeletal effects. There is also evidence that moderate intense school-based physical education classes do increase the level of physical activity and improve the physical fitness (26).…”
Section: Introductionmentioning
confidence: 99%
“…The so far published prospective controlled exercise intervention studies, most elegant support this view (14)(15)(16)(18)(19)(20), whereas similar effects could not be found in the post-pubertal period (12). Furthermore, published data indicate that the physical activity ought to include high-impact activities (21)(22)(23)(24) and that the training should probably be initiated before or in early puberty (25), if the purpose is to reach the most beneficial anabolic skeletal effects. There is also evidence that moderate intense school-based physical education classes do increase the level of physical activity and improve the physical fitness (26).…”
Section: Introductionmentioning
confidence: 99%
“…In growth or adaptation they change the shape of trabecular morphology and adapt it to external loading direction and magnitude 7,41,43 in a process called 'modeling'. 12 In adulthood the tissue is continuously renewed by the same cells in a process called 'remodeling'.…”
Section: Introductionmentioning
confidence: 99%
“…All subjects were physically active college students, as the majority of them belonged to a college sports club, though they were not initially selected based on physical activity. This may account for the improved bone quality of this group, since physical activity positively correlates with bone status (27,28).…”
Section: Discussionmentioning
confidence: 91%
“…Ohta et al (30) reported that the 25-OH-D level in 274 Japanese women aged 19-25 years was 18.7±4.8 ng/ml. As with bone quality, the physical activity of the subjects may contribute to the vitamin D status (27,28), though it is unknown whether subjects in the Ohta et al study were more physically active.…”
Section: Discussionmentioning
confidence: 99%